CASE SERIES: EFFICACY OF THROMBOLYSIS USING INTRAVENOUS ALTEPLASE IN ACUTE ISCHEMIC STROKE WITH ONSET LESS THAN 6 HOURS (CODE STROKE) - Maskuri, Fajar; Ning Tyas, Humaera Elphananing; Evicennianing Tyas, Rosyida; Wiastuti, Arni; Akhsani, Fathiya; Yudo Pratama, Yanasta (MNJ (Malang Neurology Journal), 2024)
Background: The gold standard therapy for acute ischemic stroke is timely reperfusion of ischemic brain tissue. Intravenous thrombolysis with tPA is the only proven medical therapy for acute ischemic stroke within 4.5 hours of symptom onset using intravenous alteplase at a dose of 0.9 mg per kilogram of body weight. Hemorrhagic transformation is one of the complications of thrombolytic therapy and East Asian population having a higher prevalence of cerebral hemorrhage. This study will examine several cases of ischemic stroke that were treated with thrombolysis using a standard dose (0.9 mg/kg) of intravenous alteplase in acute ischemic stroke with an onset of less than 6 hours in the Special Region of Yogyakarta, especially at the UGM Academic Hospital. Objective: To determine the efficacy of standard dose thrombolysis using intravenous alteplase (rTPA-recombinant tissue plasminogen activator) in acute ischemic stroke with an onset of less than 6 hours through activation of the Code Stroke. Methods: Descriptive research design using a case series, the hyperacute stroke patients with an onset of less than 6 hours who received intravenous alteplase which were then assessed by the National Institutes of Health Stroke Scale (NIHSS) score at initial admission, 24 hours post-alteplase and 30 days post -alteplase. The study took place and was conducted from May to October 2022 by administering intravenous alteplase at a dose of 0.9 mg/kg body weight in acute ischemic stroke patients at UGM RSA who are eligible for thrombolysis therapy with a maximum administration time of 6 hours after stroke onset with the maximum dose of alteplase is 50 mg. Results: The study sample was 8 patients with acute ischemic stroke who were treated between May to October 2022. There were 2 patients who died before completing the 3-month follow-up. One of the patients died within the second week of treatment from sepsis which may have occurred from a pre-existing pneumonia. Another patient died from ileus that occurred 1 month after tissue plasminogen activator (tPA). However, the patient with this ileus showed clinical improvement at the 24-hour post-tPA follow-up, i.e. the initial NIHSS score of 12 improved to an NIHSS score of 6. Conclusion: The modified Alteplase dose, which is 0.9 mg/kg body weight with a maximum dose of 50 mg, at the onset of stroke less than 6 hours can be an option to maximize thrombolytic therapy while still considering the efficiency of treatment costs.